DETERMINANTS OF SERVICE QUALITY ON ISLAMIC BANKS CUSTOMER SATISFACTION IN SURAKARTA - Hasyim, Fuad (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2021)
This study aims to determine the effect of Banking Service Quality (BSQ) as a derivative of SERVQUAL research on customer satisfaction at Bank Syariah Indonesia Surakarta Branch Office. The sample was taken by convenience sampling technique and got 96 respondents. The data collection instrument is a questionnaire. The results showed that three of the six dimensions of the BSQ which include effectiveness and assurance, access and reliability have an effect on customer satisfaction. While the other three, namely price, tangibles and services portfolio have no effect on customer satisfaction.